Infrastructure finance in Europe: Composition, evolution and crisis impact - Rien Wagenvoort; Carlo de Nicola; Andreas Kappeler (EIB Papers, 2010)
This article is the first attempt to compile comprehensive data on infrastructure finance in Europe. We decompose infrastructure finance by institutional sector (i.e. public versus private) into its main components, which consist of traditionalpublic procurement, project finance and finance by the corporate sector, and analyse how the roles of the public and private sectors in financing infrastructure have evolved over time, especially during the recent economic and financial crisis. In contrast with government finance that is slightly up, private finance, in particular project finance through Public-Private Partnerships, has fallen substantially during the recent crisis, reversing, at least temporarily, the longer-term trend of more private and less public financing of infrastructure.
Keywords: 330